2018
DOI: 10.1007/s00464-018-6590-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prediction model for tumor progression in Barrett’s esophagus

Abstract: Background Individuals with Barrett’s esophagus (BE) are at increased risk of high-grade dysplasia (HGD) and esophageal adenocarcinoma (EAC), but the cost-effectiveness of general surveillance of BE is low. This study aimed to identify a risk prediction model for tumor progression in individuals with BE based on age, sex, and risk factors found at upper endoscopy, enabling tailored surveillance. Methods This nested case–control study originated from a cohort of 8171 adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…41 Other nonvalidated models using clinical variables have included the presence of esophagitis, lack of PPI use, being overweight, increasing age, and a known duration of BE of 10 years. [42][43][44][45][46] The panelists noted that several additional models were currently in development and noted that models incorporating both clinical and biomarker parameters would likely ultimately be needed to optimize predictive accuracy.…”
Section: Risk Stratification Of Barrett's Esophagusmentioning
confidence: 99%
“…41 Other nonvalidated models using clinical variables have included the presence of esophagitis, lack of PPI use, being overweight, increasing age, and a known duration of BE of 10 years. [42][43][44][45][46] The panelists noted that several additional models were currently in development and noted that models incorporating both clinical and biomarker parameters would likely ultimately be needed to optimize predictive accuracy.…”
Section: Risk Stratification Of Barrett's Esophagusmentioning
confidence: 99%
“…There are several completed clinical trials focused on the effectiveness of well-known drugs used in the chemoprevention of BE and EAC [ 28 , 29 ]. However, taking into account that BE and EAC development is based on long-term and chronic exposure to GERD, these basic and clinical research areas are difficult to handle under experimental conditions [ 30 ]. Nevertheless, several in vitro and in vivo animal models of GERD leading to BE were developed [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The source cohort included all 8185 patients aged >18 years with Barrett's esophagus identified in the Swedish Patient Register (by the International Classification of Diseases [ICD] code K227) during the study period. As part of a case-control study nested within the source cohort, endoscopy and histopathology reports from 1368 patients with Barrett's esophagus at 83 endoscopy centers were retrieved and reviewed [8]. Based on this review, 299 patients with dysplastic Barrett's esophagus, according to the histopathology reports, were considered for this study, identified from 50 centers.…”
Section: Methodsmentioning
confidence: 99%